The annealing of high - level doped materials on the base of the n – and p – Si₀.₇ Ge₀.₃ solid solution under reactor irradiation - Dolgolenko, A.P. (Вопросы атомной науки и техники, 2006)
N- and p-type samples of Si-Ge solid solution with the resistivity of (4...7) 10⁻³⋅ Ohm·cm, unannealed after high-temperature baking have been investigated. Samples were irradiated up to the fluence ~10²⁰ n⁰·cm⁻² in reactor active zone at the temperature ~500 ºC in mixed neutron field. It has been observed that in the process of reactor irradiation not only phosphorus or boron precipitation, but the annealing of samples occurs resulting in the increase of doped substituting impurities solubility and hence in the reduction of resistivity. It is shown that the radiated redistribution can be described by diffusion and relaxation processes. The dose dependence on resistivity as a function of fast-pile neutron fluence was calculated and interpreted in terms of the effective medium theory. Activation energies of the doping impurities annealing process and characteristic dimensions of defect clusters have been defined.